A Novel Measure of Moral Boundaries: Testing Perceived In-Group/Out-Group Value Differences in a Midwestern Sample - Rengin Firat; Hye Won Kwon; Steven Hitlin (Sage Publications, Inc., 2022)
The literature on group differences and social identities has long assumed that value judgments about groups constitute a basic form of social categorization. However, little research has empirically investigated how values unite or divide social groups. The authors seek to address this gap by developing a novel measure of group values: third-order beliefs about in- and out-group members, building on Schwartz value theory. The authors demonstrate that their new measure is a promising empirical tool for quantifying previously abstract social boundaries. Results from a midwestern sample show an important dichotomy such that in-groups were attributed the more positive and altruistic transcendence and openness values, while out-groups were associated conservation and enhancement, the value domains revolving around a self-focus and social restraint. Furthermore, religious attendance and political ideology also emerged as strong predictors of value boundaries, whereas socioeconomic indicators were less influential. Significance and implications are discussed.